2018
DOI: 10.1186/s12887-018-1301-x
|View full text |Cite
|
Sign up to set email alerts
|

A formative study exploring perceptions of physical activity and physical activity monitoring among children and young people with cystic fibrosis and health care professionals

Abstract: BackgroundPhysical activity (PA) is associated with reduced hospitalisations and maintenance of lung function in patients with Cystic Fibrosis (CF). PA is therefore recommended as part of standard care. Despite this, there is no consensus for monitoring of PA and little is known about perceptions of PA monitoring among children and young people with CF. Therefore, the research aimed to explore patients’ perceptions of PA and the acceptability of using PA monitoring devices with children and young people with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 32 publications
5
54
0
Order By: Relevance
“…The included studies were published between 2008 and 2018. One study was conducted in Australia,38 three in Canada,39–41 two in USA,42 43 and one in the UK 44. All studies reported the use of semistructured interviews.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies were published between 2008 and 2018. One study was conducted in Australia,38 three in Canada,39–41 two in USA,42 43 and one in the UK 44. All studies reported the use of semistructured interviews.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported the use of telephone interviews 43. Methods of analysis included interpretive phenomenology,38 44 thematic analysis,40 42 43 grounded theory41 and case study analysis 39. The rationale for the conduct of the work was to increase understanding of physical activity among children with CF,38 promote children’s participation in research38 and to inform the development of interventions to promote physical activity 40–43…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations